Didactics of augmented reality in increasing the English vocabulary of university students - Arévalo Tuesta, César Augusto (2025)
English is an Indo-European language. Its history began with the arrival of the Germanic invaders in the British Isles (500 BC). Today, its dominance as a hegemonic language has spread throughout the world. In terms of the use of English as a second language, Peru ranks 58th out of 100 countries. The results are expected to be different when Spanish speakers in the EBR participate for the first time in the PISA 2025 Foreign Language Assessment Framework. It is for this reason that the present study, with a quantitative approach and a quasi-experimental design, proposes augmented reality (Mondly AR) as an effective didactic resource that increases the basic vocabulary of those who undertake the difficult task of speaking English. To evaluate the relevance of the proposal, a sample of 120 participants from the Faculty of Humanities of the Universidad Nacional Federico Villarreal was selected and divided into two groups: control and experimental. After applying the intervention program, a Mann-Whitney U of 616.000, a Wilcoxon W of 2446.000 and a Z of -6.235 were obtained in the post-test. This, at a significance level of less than 0.05, demonstrates the hypothesis proposed.